Komposisi Jenis Burung Pengunjung Ficus spp. di Kawasan Gunung Ungaran Jawa Tengah - Febriyanto, Mahendra Noor; Abdullah, Muhammad; Tri Martuti, Nana Kariada; Priyono, Bambang (Universitas Negeri Semarang, 2020)
Ficus is a genus of woody plants belonged to the family Moraceae. There are about 72 species of Ficus on the Java island. Ficus has many benefits to the ecosystem, which one is the fruit of Ficus is a source of food for many animals (frugivores), especially birds. The purpose of this study was to determine the composition of bird species that visited several species of Ficus in the mount Ungaran. The method used in this research is the observation method. From the results of the preliminary survey, determined 6 species of fig as a sample tree to be observed. Observations were made at 06:00 - 10:00 and 15:00 - 17:00. Based on the results of the study, we found 28 species of birds from 16 families who visited fig. The observations showed four different bird activities, namely only perching, eating fruit, eating insects and eating both fruit and insects. The number of bird species of fig visitors consist of 7 species of birds only perching, 8 species eating insects, 11 species eating fruit and 2 species eating both fruit and insects Ficus merupakan salah satu genus dari tumbuhan berkayu yang termasuk dalam famili Moraceae. Terdapat sekitar 72 jenis Ficus di pulau Jawa. Ficus memiliki banyak manfaat terhadap ekosistem, salah satunya adalah buah dari Ficus merupakan sumber pakan bagi banyak satwa (frugivora) terutama burung. Tujuan dari penelitian ini adalah untuk mengetahui komposisi jenis burung yang mengunjungi beberapa jenis Ficus di kawasan gunung Ungaran. Metode yang digunakan dalam penelitian ini adalah metode pengamatan. Dari hasil survei pendahuluan, ditentukan 6 jenis Ficus sebagai pohon sampel untuk diamati. Pengamatan dilakukan pada pukul 06.00 – 10.00 dan 15.00 – 17.00. Berdasarkan hasil penelitian dijumpai 28 jenis burung dari 16 famili yang mengunjungi Ficus. Hasil pengamatan menunjukkan empat aktivitas burung yang berbeda, yaitu hanya bertengger, memakan buah, memakan serangga, serta memakan buah dan serangga. Jumlah jenis burung pengunjung Ficus terdiri atas 7 jenis burung hanya bertengger, 8 jenis memakan serangga, 11 jenis memakan buah, serta 2 jenis memakan buah dan serangga.